Integrasi Nilai-Nilai Moderasi Beragama dalam Perencanaan Kurikulum PAI di Era Society 5.0 - Agus; Agus Setiawan; Ainur Alam Budi Utomo; Rahmat Riyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The PAI curriculum currently plays a strategic role in shaping student character, especially in facing the challenges of the Society 5.0 era which demands inclusive, tolerant and respectful attitudes. This research aims to examine the integration of religious moderation values in Islamic Education curriculum planning at SMPIT Manbaul Ulum. This research uses a qualitative approach with a case study method, as well as data collection through in-depth interviews with school principals, teachers, and classroom observations. The data analysis technique used is triangulation to ensure the validity and legitimacy of the findings. The research results show that SMPIT Manbaul Ulum has succeeded in integrating the values of religious moderation in the PAI curriculum, with an emphasis on tolerance, mutual respect and inclusivity. However, there are challenges related to a deeper understanding of the application of moderation values by some teachers. Some teachers expressed the need for further training to improve their competence in teaching the value of moderation. In learning practice, various methods such as discussions, simulations and case studies are used to invite students to explore relevant social issues. The implication of this research is the need for training for teachers in teaching the value of religious moderation and the development of more in-depth learning materials to create a better generation. tolerant and harmonious in the era of Society 5.0.